Difference model quantification of coseismic landslide erosion and deposition to improve connectivity metrics after the 2016 Kaikōura earthquake - Katie Jones; Jamie Howarth; Chris Massey; Pascal Sirguey; Biljana Luković (Geomorphology, 2026)

An alternative to landslide volume-area scaling relationships: an ensemble approach adopting a difference model to estimate the total volume of landsliding triggered by the 2016 Kaikōura earthquake, New Zealand - Katie E. Jones; Jamie D. Howarth; Chris I. Massey; Biljana Luković; Pascal Sirguey; Corinne Singeisen; Caleb Gasston; Regine Morgenstern; William Ries (Landslides, 2025)
Evaluating the influence of earthquakes on erosion, landscape evolution, and sediment-related hazards requires quantifying the number, location, and volume of co-seismic landslides following large earthquakes. Direct measurements of individual landslide volumes are difficult to accomplish and, as a result, rarely attempted. As an alternative, power-law scaling relationships between landslide volume and area—derived from global landslide inventories—are often used to estimate landslide volumes. The accuracy of the volume estimates derived from using these global scaling relationships remain untested and could be a source of significant uncertainty. Here, an ensemble method, adopting a pre- to post-event 2 by 2 m difference model covering an area of 6875 km 2 , has been developed to accurately estimate the volume of the > 30,000 mapped landslides triggered by the 2016 Mw 7.8 Kaikōura earthquake New Zealand. Our ensemble method estimates the total landslide volume for the Kaikōura earthquake to be 241 (+ 100/ − 69) M m 3 . This newly quantified total volume estimate of co-seismic landsliding was then compared to the total volumes estimated using globally and locally derived scaling relationships, which were found to underestimate the total landslide volume by up to 52%. As an alternative, we recommend that landslide volumes be estimated by sampling directly from high-quality empirical datasets of individual landslide volumes with similar triggering and physiographic settings.

Spatial dynamics and drivers of recent changes in grass and shrub cover in submontane grassland plant communities - Xiaobin Hua; Ralf Ohlemüller; Pascal Sirguey (Community Ecology, 2024)
Shrub encroachment into grassland ecosystems has been increasingly observed and documented worldwide in recent years. A grass–shrub transition can affect the diversity, abundance and functional integrity of grassland plant communities and understanding the drivers behind these processes is therefore crucial. While potential environmental drivers are often investigated, the role of spatial patterns of neighbouring shrub density in local shrub encroachment has been less well studied. The aim of this study is to investigate the relative role of neighbouring shrub density and topography as potential key drivers of shrub encroachment in a typical montane grassland ecosystem in New Zealand. We used the SPOT (Satellite Pour l’Observation) 6/7 multispectral imagery captured on one day in 2013 and in 2017 to calculate recent changes in shrub/grass cover during this period. Using the Normalised Difference Vegetation Index (NDVI), we classified the study area into grassland and shrubland and quantified the extent and change in these two land-cover types over the study period. We then investigated the relationships between changes in land cover and neighbourhood shrub density, elevation and aspect. Between 2013 and 2017, there was an overall shrubland increase of + 0.35% of the study area per year, and grassland decrease of −0.43% per year. Locations at which any change in vegetation type occurred were more likely to be at mid-elevation (c. 600–1,000 m a.s.l.) and on west-facing slopes. Highest shrub expansion rates were observed on areas that were on warmer, north-facing slopes and at elevations below 900 m a.s.l.; this is consistent with areas below the pre-human, natural treeline which is estimated to be at very similar elevations. We found a marked threshold in the degree to which neighbourhood shrub density correlated with local shrub encroachment: local shrub encroachment only occurred when shrub cover in the neighbourhood exceeded 40% and peaked at c. 60% indicating the potential for a sudden grass–shrub regime shift once shrub cover reaches a certain level. Our study provides new evidence from the Southern Hemisphere of a measurable and interacting effect of topography and neighbourhood shrub density on recent shrub encroachment rates in montane grasslands even over short time periods.

Measuring landslide-driven ground displacements with high-resolution surface models and optical flow - Ellorine Carle; Pascal Sirguey; Simon C. Cox (Computers & Geosciences, 2023)

Corrigendum: Inexpensive Aerial Photogrammetry for Studies of Whales and Large Marine Animals - Stephen M. Dawson; M. Hamish Bowman; Eva Leunissen; Pascal Sirguey (Frontiers in Marine Science, 2018)

Inexpensive Aerial Photogrammetry for Studies of Whales and Large Marine Animals - Stephen M. Dawson; M. Hamish Bowman; Eva Leunissen; Pascal Sirguey (Frontiers in Marine Science, 2017)

Atmospheric circulation drivers of lake inflow for the Waitaki River, New Zealand - Daniel G. Kingston; Clare S. Webster; Pascal Sirguey (International Journal of Climatology, 2016)
Hydro‐electricity is a critical resource in New Zealand, and as such improved understanding of the drivers of water resource availability is a key research goal. Large‐scale atmospheric circulation is the principal driver of surface climate and water resource variability over New Zealand. Focusing on the Waitaki River (located in the South Island; one of the most important rivers for hydro‐electricity in New Zealand), a comprehensive analysis is presented of the large‐scale atmospheric circulation drivers of monthly inflow to the three main headwater lakes, Ohau, Pukaki and Tekapo. Analyses are undertaken using composite, correlation, partial least‐squares ( PLS ) regression and cross‐wavelet analyses. Environment‐to‐climate composite analysis indicates that variation in lake inflow is driven primarily by the strength of the NE–SW pressure gradient over the three lakes (i.e. parallel to the axis of the Southern Alps, from which the lakes are fed). Relatively strong winds from a north‐westerly direction are associated with high lake inflow; weaker winds from a more south‐westerly direction occur during times of low inflow. Climate‐to‐environment composites of lake inflow, together with correlation, PLS and wavelet analysis, indicate that inflow is described well by the MZ1 and MZ2 New Zealand‐based circulation indices, but not larger‐scale modes of atmospheric circulation. The MZ1 and MZ2 indices have rarely been considered previously as explanatory variables for water resources in the South Island of New Zealand, but here it is suggested that these indices represent a promising new direction for future studies, particularly relating to season‐ahead prediction of water resource availability.

Simple correction of multiple reflection effects in rugged terrain - Pascal Sirguey (International Journal of Remote Sensing, 2009)